'Finding a voice': utilising Tronto's ethic of care framework for developing students' attentiveness to voice in a university module. Issue 1 (2nd January 2022) - Reid, James; Kaneva, Dimitrina
ABSTRACT: There has been little explication of how university lecturers who are responsible for educating future practitioners approach the complexity and conceptual messiness of 'voice'. There are dangers of objectification if curricula simply foreground the UNCRC and are only concerned with utterances and the need to listen to children. This paper explores our conceptual approach to avoid this and a limiting conceit by ignoring our own power. Specifically, we work from a feminist standpoint; in particular, we foreground Tronto's [1993. Moral Boundaries. A Political Argument for an Ethic of Care . London: Routledge. ISBN: 978-0415906425] ethic of care as the foundation for student learning in our 'Finding a Voice' module. The framework recognises the diverse needs of different participants in the module – students, lecturers, the university, and the young children who are absent from the university classroom yet who are the subject of learning – and posits understanding voice as a relation between discourse, its organising power and the social practices of people. The module explores the complexity of voice and recognises the bifurcated nature of the students' experience. They are simultaneously required to be attentive to how they action children's voice in undertaking a small piece of research with children for assessment while being conscious of their own voice. The focus here is on our attentiveness to voice in the application of learning involving a conceptual framework and our and our students' work. There are dangers, in the complexity and conceptual messiness of voice, of objectification if curricula simply foreground the UNCRC and are only concerned with utterances and the need to listen to children.